The new economics and the old economists - Davis, J. Ronnie (Ames, Iowa : Iowa State University Press, 1971)
This book is a study in history of economic thought. It deals with much recent events than most investigations of history of economic thought. This book deals with the viewpoint of the entire American economics professions during a rather short period of years.
A revision of the author's thesis, University of Virginia, 1967.
Includes bibliographical references.
rpm 23/06/2017
Loans
Keywords: Economics; Economics $1 (BUnited States $1 (BHistory.s; Economists; Economists $1 (BUnited States.s; United States $1 (BEconomic history & conditions $1 (B20th c.s; United States